Developmental sequence of young children's understanding of “knowing,” “forgetting,” and “remembering” - Uehara, Izumi (Frontiers in Psychology, 2025)
This study focused on examining young native Japanese children's linguistic understanding of words associated with awareness of one's memory, such as “know,” “forget,” and “remember,” to explore the early developmental process of metamemory. To assess whether 4-, 5- and 6-year-olds understand these words, we created new tasks for “know” and “remember,” and used a modified episodic task for “forget,” adapted from a question used in previous research concerning the state of “placing something and forgetting it.” A total of 114 children, with 38 children in each age group, participated in this study. More than 80% of the 6-year-olds understood the mental states of “knowing,” “forgetting,” and “remembering,” whereas 4-year-olds did not. The performance of 5-year-olds fell between that of the 4- and 6-year-olds, with half failing to understand “remembering” and 30% failing to understand “forgetting.” These findings indicate a developmental progression in understanding, in the order of “know,” “forget,” and “remember.” The tasks developed in this study will contribute to future research on cognitive development, as well as to educational and support practices for young children.